Tildrakizumab for the treatment of psoriasis. (21st September 2018) - Bangert, Christine; Kopp, Tamara
Psoriasis is a chronic skin disorder driven by IL-23 and the downstream T-helper cell 17 (Th17) pathway. Tildrakizumab is a humanized monoclonal antibody selectively targeting the p19 subunit of IL-23, a key cytokine for Th17 cells. Here, we provide an overview of IL-23 in the context of psoriasis pathogenesis and review the results of the Phase I, II and III clinical trials for tildrakizumab in patients with moderate-to-severe chronic plaque psoriasis in order to assess its efficacy, safety and clinical usefulness. In all clinical trials, tildrakizumab demonstrated significant clinical improvement and a favorable safety profile. In Phase III trials, 75% of tildrakizumab-treated patients reached a Psoriasis Area and Severity Index 75 at week 28 demonstrating superior efficacy as compared with etanercept treatment. The tildrakizumab-induced reduction in skin inflammation proves the important pathogenic role of IL-23 in psoriasis and further supports the utility of drugs targeting the IL-23/Th17 pathway. Targeting IL-23p19 with tildrakizumab augments the therapeutic repertoire for patients with moderate-to-severe chronic plaque psoriasis.